(untitled) (Research, Society and Development, 2024)
The professional nurse has an essential role in the articulation of humanized and quality care, aiming at promoting the health of the neonate, where humanization becomes more important since feelings such as stress can arise due to the permanence of the patient and family within the care unit. In this sense, the present research has as main objective to analyze, through bibliographic research, the importance of humanized nursing care in neonatal intensive care units. this is an integrative literature review study based on scientific nursing publications indexed in the Scientific Electronic Library Online and Virtual Health Library database between the years 2018 and 2022. After the searches carried out in the scientific literature regarding the humanized nursing care for the newborn in the intensive care unit, two categories of analysis were used: (1) The importance of the nursing team in the recovery of the newborn; (2) Attributions of the professional nurse in relation to the newborn hospitalized in the ICU. The creation of actions that enable this bond between professional-family, I have a greater sensitivity in the health-disease process, where the team that provides assistance needs to create this bond so that they also feel cared for and promote a greater bond of trust.